EK θ multilevel inverter – a minimal switch novel configuration for higher number of output voltage levels. Issue 13 (1st October 2020) - Bhaskar, Mahajan Sagar; Meraj, Mohammad; Iqbal, Atif; Ben‐Brahim, Lazhar; Padmanaban, Sanjeevikumar; Abu‐Rub, Haitham
Abstract : In this study, a new multilevel inverter (MLI) configuration is proposed to generate higher number of levels with minimal control switches. The proposed inverter's nomenclature is E K θ MLI, termed from its stems of shape. Conventional single‐phase H‐bridge module is modified to design the structure of θ MLI called 'θ cell' (where, K  = 0) by incorporating three symmetrical DC‐sources and replacing one leg of H‐bridge by bidirectional switches. The θ cell of the proposed E K θ MLI generates five‐level AC waveform at the output by using only four controlled switches (two unidirectional and two bidirectional). Therefore, the size, cost and switching logic of the MLI is reduced. The basic structure of E K θ MLI called 'Eθ MLI' (where K  = 1) is designed which is capable of generating seven‐level. For further extension, double‐switch‐E cell (DS‐E cell) is added in the middle and each DS‐E cell increases the four levels by utilising two bidirectional switches and two DC supplies. The generalised MLI configuration is explained in niceties to generate a higher number of levels (more than 5). The modes of operation, voltage across the switches, power losses of E K θ are discussed. The proposed MLI is experimentally investigated using level shifting pulse width modulation.